A representação midiática de Luis Suárez na imprensa uruguaia (2010-2014) - Lima, Pamella Moreira (2018)
This research aims to analyze the role of press narratives in the construction of the image of idolatry of Uruguayan soccer player Luis Alberto Suárez Díaz. The objective of this study is to analyze the media representation of the attacker between the 2010 and 2014 World Cups. Our objective is to find out what type of idol and characteristics of the striker are highlighted in the narrative discourse of the sport s supplement of the newspaper El País: Ovación. The work will result from a content analysis process of the journal's editions during the following competitions: World Cup 2010, Copa America 2011, Olympic Games 2012 and World Cup 2014